Pemodelan Sistem Informasi Geografis untuk Pemetaan Kesesuaian Wilayah Perairan dan Pesisir Selat Madura - Hidayah, Zainul; Wiyanto, Dwi Budi (Rekayasa, 2021)
The coastal area of the Madura Strait stretches from Surabaya City to the east to Situbondo Regency and includes the southern part of Madura Island. The aim of this research is to map the suitability of the waters and coastal areas of the Madura Strait using GIS modeling. Mapping of the designation of the waters and coastal areas of the Madura Strait was carried out by overlaying spatial data covering bio-physical parameters including water transparency, pH, water substrate, temperature, salinity, and depth. The designation of water areas is divided into three classes, namely capture fisheries, tourism and conservation purposes. The spatial data used comes from several sources, namely the results of water quality surveys, Landsat 8 satellite imagery, bathymetry data / sea depth and Rupa Bumi Indonesia (RBI) maps at a scale of 1: 25,000. For water quality data comes from the results of a survey by the Marine and Fisheries Service of East Java Province in 2019 at 78 observation points in the waters of the Madura Strait. Water quality parameters used in GIS modeling are pH, salinity, brightness and temperature. The data for each observation point were then interpolated using the Kringing method. Landsat 8 satellite imagery is used to map the condition of the bottom substrate waters. Meanwhile, the depth data was downloaded from GEBCO (General Bathymetric Charts of the Oceans). The result of overlaying thematic maps shows that 37.69% (8586.69 km2) of the area of the Madura Strait is suitable for capture fisheries activities, then 10.28% (2341.02 km2) is suitable for marine tourism areas and 19.06 % (4343.4 km2) suitable for conservation areas. Meanwhile, 32.97% (7511.94 km2) can be used as conservation and tourism areas.